Health Status and Medical Treatment of the Future Elderly Final Report - Goldman, Dana P. (RAND Corporation, 2004)
To help the Centers for Medicare and Medicaid Services more accurately predict future health care costs, RAND Health developed the Future Elderly Model (FEM). A demographic-economic model of health spending projections, the FEM enables the user to answer "what-if" questions about the effects of changes in health status and disease treatment on future health care costs. This report describes the development of the FEM and its application in four key clinical areas.